Estudos Cinéticos da aquação do trans-[Co(en)2Cl2]Cl - Moura, Aline O. (2006)
The trans-dichlorobis(ethylenediamine)cobalt(III) chloride was synthesized in an undergraduate laboratory and its aquation reaction was carried out at different temperatures. This reaction follows pseudo-first-order kinetics and the rate constants, determined at 25, 35, 45, 55 and 70 º C, are 1.44 x 10-3; 5.14 x 10-3; 1.48 x 10-2; 4.21 x 10-2 and 2.21 x 10-1 s-1, respectively. The activation energy is 93.99 ± 2.88 kJ mol-1.